Communicating the Value of Ergonomics to Management – Part 1: Language, ROI, and Models. (September 2017) - Rempel, David; Reid, Christopher R.; McGowan, Blake; Williamson, Cindy; Alexander, David; Whitehead, Cindy; Sobhani, Ahmad
More than ever, human factors engineers and ergonomists need to justify our practice's value to management. How can we effectively communicate with management? How should we present a Return on Investment (ROI) that leadership will find useful that addresses company profits, cost savings, productivity, first time quality, and turnover? What else does management care about other than ROI? The presenters on this first panel of a two panel set, will share their years of experience on how to effectively communicate the value of HF/E to management, industrial designers, and engineers. The session will start with a lecture followed by a panel discussion led by the moderators. The audience will be encouraged to participate with their own questions and comments.